O despertar da protagonista feminina de Kate Chopin - França, Ana Paula Oliveira (Brasil, 2024)
This research aims to analyze how the protagonist Edna Pontellier, of the novel The Awakening, of Kate Chopin, (1899), cab be seen as a woman ahead of her time, emphasizing which actions show her search for freedom and independence. The methodology is bibliographic and qualitative. To the analysis, we used the theoretical approach of Virginia Woolf, Simone de Beauvoir and Elaine Showalter, analyzing what the Literary Feminist Criticism discusses about the social roles defined to women, the feminist struggles, the achievement of feminist movements. Initially, the protagonist Edna Pontelier represents the traditional portrait of the woman, as mother, wife and a model to the society of the time. But the analysis reveal that she has various oscillations, she resists to the rules of the patriarchal society, portraying what Elaine Showalter theorized about the figuration of female characters in works of female authorship, dividing it in three phases: feminine, feminist and female. Therefore, the protagonist sometimes acts as the society expects (feminine phase), sometimes she questions rules and breaks them (feminist phase), sometimes she searches her own identity (female phase). In the end, she chooses herself, an act of courage and confrontation, she commits suicide, because she sees in death her only possibility of freedom in relation to the patriarchal rules.